Evaluation of peripheral microcirculation improvement of foot after tarsal tunnel release in diabetic patients by transcutaneous oximetry. Issue 1 (13th January 2015) - Trignano, Emilio; Fallico, Nefer; CHEN, HUNG‐CHI; Faenza, Mario; Bolognini, Alfonso; Armenti, Andrea; Santanelli Di Pompeo, Fabio; Rubino, Corrado; Campus, Gian Vittorio
Abstract : Background: According to recent studies, peripheral nerve decompression in diabetic patients seems to not only improve nerve function, but also to increase microcirculation; thus decreasing the incidence of diabetic foot wounds and amputations. However, while the postoperative improvement of nerve function is demonstrated, the changes in peripheral microcirculation have not been demonstrated yet. The aim of this study is to assess the degree of microcirculation improvement of foot after the tarsal tunnel release in the diabetic patients by using transcutaneous oximetry. Patients and methods: Twenty diabetic male patients aged between 43 and 72 years old (mean age 61.2 years old) suffering from diabetic peripheral neuropathy with superimposed nerve compression underwent transcutaneous oximetry (PtcO2) before and after tarsal tunnel release by placing an electrode on the skin at the level of the dorsum of the foot. Eight lower extremities presented diabetic foot wound preoperatively. Thirty‐six lower extremities underwent surgical release of the tibialis posterior nerve only, whereas four lower extremities underwent the combined release of common peroneal nerve, anterior tibialis nerve, and posterior tibialis nerve. Results: Preoperative values of transcutaneous oximetry were below the critical threshold, that is, lower than 40 mmHg (29.1 ± 5.4 mmHg). PtcO2 values at one month after surgery (45.8 ± 6.4 mmHg) were significantly higher than the preoperative ones (P = 0.01). Conclusions: The results of postoperative increase in PtcO2 values demonstrate that the release of the tarsal tunnel determines a relevant increase in microcirculation in the feet of diabetic patients. © 2015 Wiley Periodicals, Inc. Microsurgery 36:37–41, 2016.